Calcium-aided fabrication of pea protein hydrogels with filler emulsion particles coated by pH12-shifting and ultrasound treated protein. (April 2022) - Ma, Tiantian; Xiong, Youling L.; Jiang, Jiang
Abstract: Pea protein is a functional ingredient as well as a structure builder in meat substitution products, and the addition of calcium and inclusion of emulsified oil may improve product textural properties. In the present study, O/W emulsions prepared with pH12 -shifting (pH12 ) and high-intensity ultrasound (US) treated pea protein were imbedded into the pea protein isolate (PPI) gel matrix with or without CaCl2, and the effects on rheological, textural, and water-binding properties of the composite hydrogels were investigated. The addition of 5–20 mM CaCl2 significantly enhanced the elastic modulus and textural properties of the hydrogels (16% protein, w/v) especially with the presence of 10% emulsified oil (v/v) stabilized by pH12 or US modified PPI ( P < 0.05). The gel hardness increased with CaCl2 addition, reaching a maximum at 15 mM CaCl2 . Gels filled with pH12 and US protein emulsions had less cooking loss but increased hardness than gels filled with native protein emulsion, and CaCl2 further improved water binding. Microstructural examination revealed ordered PPI gel structures when filled with pH12 and US protein emulsions and in the presence of Ca 2+ . The NMR results suggest that water was tightly bound despite some shifting of immobilized water (T21 ) to free water (T22 ) in Ca 2+ treated PPI gels. Graphical abstract: Image 1 Highlights: pH shifting and ultrasound improve pea protein surface activity. Emulsion-filled pea protein gels have a strong mechanical strength. Calcium ions promote membrane-matrix protein interaction. Emulsion-filled calcium-included gels show excellent rheological properties.